Identification of Aerodynamic Tonal Noise Sources of a Centrifugal Compressor of a Turbocharger for Large Stationary Engines - Jiří Vacula; Pavel Novotný (Applied Sciences, 2023)
The aerodynamics of centrifugal compressors is a topical issue, as the vibrations and noise reduce the comfort of people who are in proximity to the compressor. The current trend in rotating machinery research is therefore not only concerned with performance parameters but also increasingly with the effect on humans. An analysis of aerodynamic noise based on external acoustic field measurements may be a way to assess the nature of aerodynamic excitation. In this research, the experimental measurements at 20 operating points covered the entire characteristic operating range of the selected centrifugal compressor. The dominant noise arising at blade-passing frequency (BPF) was identified at all the operational points, and the dominant effect of the buzz-saw noise was identified at the maximum rotor speed. The determination of the total sound pressure level <semantics>LP<mfenced separators="|">A</mfenced></semantics> showed a trend towards an increasingly higher rotor speed and compressor surge line. In the amplitude-frequency characteristics, the sound pressure was found to be dependent on the rotor speed for BPF. On the other hand, non-monotonicity was detected between the operational points at given speed lines, confirming the complexity of the aerodynamics of rotating machines. The metric chosen to identify prominent tones determined by the tonality of individual tones in the frequency spectrum showed a clear effect of integer multiples of the rotational frequency on the overall noise. Thus, the results presented here confirm the dominant influence of BPF in terms of the psychoacoustic impact on humans.